Theoretical Study on Cracking Moment of Normal Section of Concrete Beams Reinforced with FRP Bars - Jia, B.; Zhu, S.T.; Liu, S.F.; Liu, X. (Asian Journal of Chemistry, 2014)
The cracking moment is an important indicator to measure the crack resistance and durability of concrete beams reinforced with FRP bars. In order to establish the computational formula of cracking moment of FRP reinforced concrete beam, a sectional plasticity influence coefficient of resistance moment which could be applied to reflect the plastic deformation of concrete in tensile region, was introduced. Moreover, the value of the coefficient was obtained based on the tested experimental data collected from the literature. The theoretical results were compared to the test results of beam cracking moments, as well to the values calculated by American code ACI 440.1 R-06, it turned out that the calculation formula established in this paper had a good applicability and could provide some design guideline for the flexural members reinforced with FRP bars.